Histology and structure of the testicles in three species of Atelopus frogs (Anura: Bufonidae) endemic to the Sierra Nevada de Santa Marta, Colombia - Sánchez-Ferreira, Arantxa; Rincón-Barón, Edgar J.; Rueda-Solano, Luis A. (Revista de Biología Tropical, 2021)
Introduction: Testicular histology constitutes one of the least explored aspects in frogs of the genus Atelopus. This taxonomic group shows an alarming population decline; therefore, its reproductive biology is one of the greatest topics of interest for its conservation. Objective: To describe the testicular morphology and the spermatogenetic lineage cells in adult males of Atelopus laetissimus, Atelopus nahumae, and Atelopus carrikeri in the Sierra Nevada de Santa Marta, Colombia. Methods: During June – July 2017 and 2018, sampling was conducted in the localities of San Lorenzo and Páramo Cebolletas, Sierra Nevada de Santa Marta (SNSM), to collect 15 adult males, 5 per species. Testes samples were fixed in Bouin to be processed by the standard paraffin-embedding technique. Histological sections (3 mμ) were stained with Hematoxylin-eosin and Mallory-Heidenhain-Azan-Gomori’s. For the description and photographic register of the germ cells, the photonic microscopy technique was used with the differential interference contrast system. Results: The testes are oval organs, compact, light yellow color, and with little vascularization. Externally, they are surrounded by a thin albuginea tunic constituted by regular dense connective tissue. Inside this layer, they are composed of numerous seminiferous tubules of hexagonal contour, in which germ cell cysts are distinguished at different stages of spermatogenesis (spermatogonia I and II, spermatocyte I and II, and early and late spermatids) and spermiogenesis (spermatozoa in fascicles and free spermatozoa). Separating the seminiferous structures is the interstitial tissue in which Leydig cells and blood vessels stand out. Additionally, in the cranial part of the testis, the Bidder’s organ was found, formed by two distinguishable regions, the cortex and the medulla. In the cortex, there are previtellogénic oocytes of different sizes surrounded by a monolayer of flat follicular cells. For its part, the medullary region is the connective tissue that nourishes the oocytes and is constituted by blood capillaries. Conclusions: The gonads of the three species analyzed present a cystic cellular organization similar to other anurans, where all stages of spermatogenesis and spermiogenesis were identified, possibly indicating a continuous reproductive activity. Likewise, the Bidder’s organ is reported for the first time in the three Atelopus species, which allows suggesting a possible sexual reversion in case of a population decrease of females as a reproductive strategy.